The Detrimental Side Effects of Minimum Wage Laws3. (December 2013) - Hovenga, Claire; Naik, Devaja; Block, Walter E.
Abstract The adverse effects of minimum wage legislation demonstrate how a government policy presumably intended to help people worst off in society can actually end up causing far more harm than good. In this case, the victims are unskilled laborers. By making it illegal for employers to pay unskilled workers wages equal to their marginal revenue productivity, it causes unemployment for all workers whose productivity happens to be below the minimum wage. It also widens the wage gap between whites and minorities because there are disproportionate numbers of unskilled and uneducated minorities compared with whites.